Development scenarios for the North and Baltic Sea grid: A welfare economic analysis - Jonas Egerer; Friedrich Kunz; Christian von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The North and Baltic Sea Grid is one of the largest pan-European infrastructure projects raising high hopes regarding the potential of harnessing large amounts of renewable electricity, but also concerns about the implementation in largely nationally dominated regulatory regimes. The paper develops three idealtype development scenarios and quantifies the technical-economic effects: i) the Status quo in which engagement in the North and Baltic Sea is largely nationally driven; ii) a Trade scenario dominated by bilateral contracts and point-to-point connections; and iii) a Meshed scenario of fully interconnected cables both in the North Sea and the Baltic Sea, a truly pan-European infrastructure. We find that in terms of overall welfare, the meshed solution is superior; however, from a distributional perspective there are losers of such a scheme, e.g. the incumbent electricity generators in France, Germany, and Poland, and the consumers in low-price countries, e.g. Norway and Sweden. Merchant transmission financing, based on congestion rents only, does not seem to be a sustainable option to provide sufficient network capacities, and much of the investment will have to be regulated to come about. We also find strong interdependencies between offshore grid expansion and the subsequent onshore network.
Keywords: D60; L51; L94; 330; Electricity; Offshore Transmission; Rent Allocation